Airway management in laryngotracheal injuries from blunt neck trauma in children. Issue 2 (4th November 2015) - Chatterjee, Debnath; Agarwal, Rita; Bajaj, Lalit; Teng, Sarena N.; Prager, Jeremy D.
Summary: Pediatric laryngotracheal injuries from blunt neck trauma are extremely rare, but can be potentially catastrophic. Early diagnosis and skillful airway management is critical in avoiding significant morbidity and mortality associated with these cases. We present a case of a patient who suffered a complete tracheal transection and cervical spine fracture following a clothesline injury to the anterior neck. A review of the mechanisms of injury, clinical presentation, initial airway management, and anesthetic considerations in laryngotracheal injuries from blunt neck trauma in children are presented.